Crossing the Ya-Lu River: Chinese economic activities in North Korea Post-2002 - GAO, Bo (2017)
This thesis examines the effectiveness of China’s economic activities in North Korea in terms of resolving China’s domestic non-traditional security problems. It studies the implementation of China’s foreign economic policy towards North Korea. The thesis uses qualitative research methodology to study the economic activities launched after 2002 near the Sino-DPRK border and in North Korean ocean territory. It hypothesises that the commercialisation of China’s foreign economic policy towards North Korea is driven by actors below the state in order to resolve their socio-economic problems at the sub-state level. This policy-transition from original pro-aid economic policy to North Korea also has important implications for the regional order in Northeast Asia. These implications include advancing the economic reform process in North Korea, worsening the relationship between China and South Korea, and reducing the effectiveness of the international effort to denuclearise North Korea. The specific non-traditional security problems which have driven three major sectors of China’s economic activities in North Korea, i.e. mineral resource and energy sector, fishery industry sector and cross-border activities sector, include issues such as environment pollution, resource scarcity, labor shortage and cultural decline that diverge from the China’s strategic targets to Korea Peninsular. This thesis explores the link between high and low politics in the implementation stage of Chinese foreign policy through the relatively active role of actors below the state in Sino-DPRK economic cooperation and their impacts at the regional level after 2002 in contrast to the previous dominant role of central government in this field.